Buckling and Deflection of Ice Sheet Caused by Ship - Koto, J; Afrizal, Efi; M.A, Wahid (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
The movement of ice ship gradually gives load to the ice sheet, along with that, the ice sheet will react in proportion to the load of the ship. The phenomenon of interaction between ice and hull of ship has been studied by researchers through empirical mathematical simulation and experiment. This paper discusses the phenomena of ice sheet buckling and deflection caused by a ship sailing in ice level. The ice sheet buckling and deflection is analyzed based on using Finite Element Method based on Euler and Cantilever methods. The methods were described from general deflection equation for a beam. Simulation was carried out using Abaqus running ahead and astern at several speeds of 0.4m/s, 0.5m/s and 0.6m/s.